Effects of n-grams on the rated L2 writing quality of expository essays: A conceptual replication and extension. (April 2021) - Zhang, Xiaopeng; Li, Wenwen
Abstract: This study examined effects of n -gram measures (i.e., range, frequency, and association strength) on the rated L2 writing quality. A corpus of 1643 expository essays were analyzed with a natural language processing tool. Results of separate regression trees showed that spoken bigram range, spoken bigram proportion 10K, academic trigram frequency, and spoken bi- and-trigram association strength (Delta P and MI) were reliably predictive of the variance in L2 writing quality. However, when indices of the range, frequency and association strength were combined, results of the regression tree indicated that spoken bigram proportion 10k, spoken trigram Delta P, spoken bigram MI, and spoken bigram range were reliable predictors for the rated L2 writing quality. These observations differed from previous ones with respect to effects of n -gram measures on the rated L2 writing quality. Such differences call for the need to systematically assess the predictive power of n -grams on L2 writing quality across genres.